2018
DOI: 10.1002/marc.201800146
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐Conductive and Thermal Properties of a Synergistic Poly(ethylene carbonate)/Poly(trimethylene carbonate) Blend Electrolyte

Abstract: Electrolytes comprising poly(ethylene carbonate) (PEC)/poly(trimethylene carbonate) (PTM C) with lithium bis(trifluoromethane sulfonyl)imide (LiTFSI) are prepared by a simple solvent casting method. Although PEC and PTMC have similar chemical structures, they are immiscible and two glass transitions are present in the differential scanning calorimetry (DSC) measurements. Interestingly, these two polymers change to miscible blends with the addition of LiTFSI, and the ionic conductivity increases with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…31 Interestingly, in a PEC electrolyte system containing Li bis(trifluoromethane sulfonyl)imide (LiTFSI), Brandell et al showed that the blending of poly(trimethylene carbonate) (PTMC) at optimized ratio can increase the conductivity as high as 10 À6 S cm À1 at 50 C, indicating that host polymers can affect the ion transport and conductivity. 32,33 To overcome the strong EO-Li + interactions, Bao et al designed a loosely coordinated poly(tetrahydrofuran) (PTHF) host that is similar to PEO but contains fewer oxygen heteroatoms in polymer backbone. 34 Due to the weakened O-Li + interactions, the crosslinked PTHF-based electrolyte shows promising conductivity of 2.9 3 10 À6 S cm À1 and a Li transference number of 0.53.…”
Section: Context and Scalementioning
confidence: 99%
“…31 Interestingly, in a PEC electrolyte system containing Li bis(trifluoromethane sulfonyl)imide (LiTFSI), Brandell et al showed that the blending of poly(trimethylene carbonate) (PTMC) at optimized ratio can increase the conductivity as high as 10 À6 S cm À1 at 50 C, indicating that host polymers can affect the ion transport and conductivity. 32,33 To overcome the strong EO-Li + interactions, Bao et al designed a loosely coordinated poly(tetrahydrofuran) (PTHF) host that is similar to PEO but contains fewer oxygen heteroatoms in polymer backbone. 34 Due to the weakened O-Li + interactions, the crosslinked PTHF-based electrolyte shows promising conductivity of 2.9 3 10 À6 S cm À1 and a Li transference number of 0.53.…”
Section: Context and Scalementioning
confidence: 99%
“…Tominaga and co‐workers studied the phase behavior and ionic conductivity of poly(ethylene carbonate) (PEC) / poly(trimethylene carbonate) (PTMC) / LiTFSI blends. [ 35 ] They observed a synergistic effect on ionic conductivity when PEC/PTMC became compatible. We believe that this can be attributed to the extremely grain size and disappearance of interphase in the compatible blends, which is in agreement with our result.…”
Section: Figurementioning
confidence: 99%
“…Due to the high crystallinity of PEO, PEO‐based SPEs have a low ionic conductivity (10 −8 –10 −7 S cm −1 ) at room temperature, which does not meet the requirement for ionic conductivity (>10 −4 S cm −1 at room temperature) of electrolytes with promising applications. [ 33,36,37 ] Many strategies, such as adding inorganic nanoparticles, [ 38–40 ] blending, [ 41 ] copolymerization, [ 42 ] and crosslinking [ 43–45 ] have been adopted to effectively suppress the crystallization of PEO and improve the ionic conductivity of PEO‐based SPEs. Coat et al [ 46 ] reported the synthesis of poly(diethylene oxide‐alt‐oxymethylene) (P(2EO‐MO)) as a polymer matrix for SPE, which has higher T g than that of PEO in the electrolyte.…”
Section: Figurementioning
confidence: 99%